PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI STATISTIKA - Kapitan, Lisma; Laamena, Christina Martha; Gaspersz, Magy (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2019)
Student learning achievement in statistical material is still relatively low, because the learning method used is still monotonous (conventional). This study aims to improve the learning achievement of class XII Students of SMA Negeri 2 Salahutu on statistical material through the cooperative learning type two stay two stray. This type of research is a class action research consisting of two cycles, with each cycle consisting of two meeting. The subjects in this study were students of class XII-MIA2 with a sample of 20 students. Data collection techniques in this study were obtained from the results of observations and final test results of students in each cycle. Classical student learning outcomes from cycle I to cycle II increased by 15%. Based on results obtained, it can be concluded that using the cooperative learning of the two stay two stray type can improve the learning outcomes of class XII students of SMA Negeri 2 Salahutu on statistical matrial.